Vitamin D assays and the definition of hypovitaminosis D: results from the First International Conference on Controversies in Vitamin D - Sempos, Christopher T.; Heijboer, Annemieke C.; Bikle, Daniel D.; Bollerslev, Jens; Bouillon, Roger; Brannon, Patsy M.; DeLuca, Hector F.; Jones, Glenville; Munns, Craig F.; Bilezikian, John P.; Giustina, Andrea; Binkley, Neil (British journal of clinical pharmacology, 2018)
The First International Conference on Controversies in Vitamin D was held in Pisa, Italy, 14–16 June 2017. The meeting's purpose was to address controversies in vitamin D research, review the data available, to help resolve them, and suggest a research agenda to clarify areas of uncertainty. The serum 25‐hydroxyvitamin D [25(OH)D] concentration [i.e. the sum of 25(OH)D3 and 25(OH)D2] remains the critical measurement for defining vitamin D status. Assay variation for 25(OH)D has contributed to the current chaos surrounding efforts to define hypovitaminosis D. An essential requirement to develop a consensus on vitamin D status is that measurement of 25(OH)D and, in the future, other potential vitamin D biomarkers [e.g. 1α,25(OH)2D3, 3‐epi‐25(OH)D, 24,25(OH)2D3, vitamin D‐binding protein, free/bioavailable 25(OH)D and parathyroid hormone] be standardized/harmonized, to allow pooling of research data. Vitamin D Standardization Program tools are described and recommended for standardizing 25(OH)D measurement in research. In the future, similar methodology, based on National Institute for Standards and Technology standard reference materials, must be developed for other candidate markers of vitamin D status. Failure to standardize/harmonize vitamin D metabolite measurements is destined to promulgate continued chaos. At this time, 25(OH)D values below 12 ng ml–1 (30 nmol l–1) should be considered to be associated with an increased risk of rickets/osteomalacia, whereas 25(OH)D concentrations between 20 ng ml–1 and 50 ng ml–1 (50–125 nmol l–1) appear to be safe and sufficient in the general population for skeletal health. In an effort to bridge knowledge gaps in defining hypovitaminosis D, an international study on rickets as a multifactorial disease is proposed.